Por caminhos de terra e de tinta: A trajetória de Carlota Carvalho, uma escritora nos sertões maranhenses (séculos XIX e XX) - Lima, Regina Celia Costa (Universidade do Vale do Rio dos Sinos, 2021)
This doctoral dissertation, entitled “By dirt and ink paths: the trajectory of Carlota Carvalho, a writer in the ‘sertões maranhenses’ (19th and 20th centuries)”, aims to investigate the trajectory of the teacher and writer Carlota Carvalho, seeking to understand the elements that constituted her intellectual life, as well as the meaning that her oeuvre “O Sertão” had for the historiography of Brazil and, in particular, for this scholar who thought about the south of the Brazilian state of Maranhão. Carlota was a normalist teacher, born in the middle of the 19th century, who worked in the literacy (“teaching of the first letters”) in the states of Pará and Maranhão. Her teaching career began in the Bailique Islands, current Brazilian state of Amapá, in the final years of the empire, and in the “sertão” of Maranhão, since the early years of the Republic. In addition to being a teacher, Carlota Carvalho was the author of an important oeuvre about the “sertão”, and of several articles related to man and woman from “sertão”, in newspapers from Maranhão, from the first half of the 20th century. Published in 1924, her book “O Sertão” had great repercussions at the time, and is still considered a reference for studies on the hinterlands of Maranhão, northern part of the state of Goiás (current Tocantins), Pará and Amapá. Carlota was also a founding partner of IHGM, in 1925, an aspect that was investigated in this work in order to discuss the relationships she maintained with other intellectuals of the period and the spaces of sociability she attended. The theoretical and methodological perspective adopted in this dissertation is linked to cultural history, establishing a dialogue with intellectual history, the history of writing and reading practices, representations, gender and women. The sources analyzed were newspapers and journals from the second half of the 19th century and the first of the 20th century, in addition to the works written by Carlota, other authors and memoirists who discuss the “sertão” of Maranhão of that epoch. The research revealed a character with a strong engagement in the cultural universe of this region of the “sertão”, with fruitful relationships with the intellectuals of her time and with the press in the second half of the twentieth century.
Keywords: Trajetória; Intelectual; Carlota Carvalho; Mulher sertaneja; Sertão Maranhense; Mulher sertaneja; Escritora maranhense; Trajectory; Intellectual; Woman from “sertão “; Writer from Maranhão; ACCNPQ::Ciências Humanas::História